Impact of the inappropriate internet usage on the musculoskeletal system and the postures of students - Dávila Benavides, Yois Amelia Sara (2018)
The globalization in the 20th and 21th centuries permitted the expansion on science, technology and computer technology and, thus, the growth of communications on Internet. But the inappropriate use by adolescents and young students could cause diseases in their musculoskeletal system as the cervicalgia, tendinitis and others, which should receive treatment, in parallel with a guidance and control from the parents and teachers of the appropriate Internet usage.